Methods in Educational Research: From Theory to Practice - Jessaca K. Spybrook (The Evaluation Center at Western Michigan University, 2008)
A review of the book Methods in Educational Research: From Theory to Practice by Maguerite G. Lodico, Dean T. Spaulding, and Katherine H. Voegtle published in 2006 by Jossey-Bass.